Oxiranyl remote anions from epoxy cinnamates and their application towards the synthesis of α,β-epoxy-γ-butyrolactones - Patpanat Sermmai (2020)
© 2020 Elsevier Ltd A series of α,β-epoxy-γ-butyrolactones were synthesized in moderate yields via oxiranyl remote anions derived from epoxy cinnamate esters. The key synthetic step involved deprotonation of the β-position of α,β-epoxy cinnamate derivatives where the generated β-anion was stabilized by remote chelation from an ester group. The substitution reaction of the anion with a variety of ketones, followed by cyclization, readily furnished the desired substituted α,β-epoxy-γ-butyrolactones.